2002
DOI: 10.2337/diabetes.51.4.1005
|View full text |Cite
|
Sign up to set email alerts
|

The Concurrent Accumulation of Intra-Abdominal and Subcutaneous Fat Explains the Association Between Insulin Resistance and Plasma Leptin Concentrations

Abstract: Obesity is associated with insulin resistance, particularly when body fat has a central distribution. However, insulin resistance also frequently occurs in apparently lean individuals. It has been proposed that these lean insulin-resistant individuals have greater amounts of body fat than lean insulin-sensitive subjects. Alternatively, their body fat distribution may be different. Obesity is associated with elevated plasma leptin levels, but some studies have suggested that insulin sensitivity is an additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
237
1
21

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(287 citation statements)
references
References 73 publications
28
237
1
21
Order By: Relevance
“…6A). This IAF depot is an important determinant of insulin sensitivity [11], which could in part be mediated by adiponectin's effect to enhance insulin action. Both age and female sex were independently associated with increased adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6A). This IAF depot is an important determinant of insulin sensitivity [11], which could in part be mediated by adiponectin's effect to enhance insulin action. Both age and female sex were independently associated with increased adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Android body fat distribution is associated with insulin resistance more than is a gynoid body fat distribution [5], with the site of abdominal fat distribution being an additional determinant of insulin sensitivity [6,7,8,9,10,11]. We found in both lean and obese subjects that the intraabdominal fat (IAF) depot is a stronger determinant of insulin sensitivity than the subcutaneous fat (SCF) depot [11], while SCF is the main determinant of the plasma concentration of leptin [11], an adipocyte-derived hormone regulating energy metabolism [12,13].…”
mentioning
confidence: 99%
“…By contrast, this effect quantitatively diminishes as intra-abdominal fat accumulates. 57 However, our empirical observation is derived from the best fit between FFM, WC and risk factors, and therefore any causal interpretation is preliminary and should be done with caution.…”
Section: Plausibility Of Adjusting Wc For Heightmentioning
confidence: 99%
“…Some reports suggest it is better correlated with subcutaneous rather than visceral fat. 46,47 However, a study conducted in monozygous twins discordant for obesity, demonstrated an association of the visceral fat area with leptin levels in men. 48 Furthermore, Tong et al 49 found that circulating leptin level predicted visceral fat accumulation at 5 and 10 years follow-up.…”
Section: Pathophysiology Of Obesity: Leptin's Rolementioning
confidence: 99%